PENEGAKAN HUKUM TINDAK PIDANA TERHADAP ANAK PASAL 81 AYAT (1) UNDANG-UNDANG NOMOR 17 TAHUN 2016 TENTANG PERLINDUNGAN ANAK - Erwansyah, Rahmad (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT Children are very vulnerable to being subject to violence. This is because children are socially and legally weak objects, so children are often used as material exploitation and impunity for crime due to the weak protection provided by both the social and state environment to children. This has led to widespread cases of violence against children occurring around the social sphere of Indonesian society. Various types and forms of violence with various variants are accepted by Indonesian children, such as murder, rape, molestation, torture, trafficking, abortion, pedophilia, and various exploitation of children in the fields of work, neglect, kidnapping, child escape and hostage taking. In Indonesia, there is already a law that regulates issues concerning children, namely Law Number 17 of 2016 concerning the Establishment of Government Regulations in lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 Concerning Child Protection into Law - Law, where in law enforcement this Act is the basic reference in the imposition of sanctions or penalties for perpetrators of sexual intercourse against minors. Based on the background described above, the authors formulate the problem as follows: (1) How is the protection of children in law enforcement criminal acts Article 81 Paragraph (1) of Law Number 17 Year 2016 concerning Child Protection? (2) How is the criminal law enforcement against Children in Article 81 Paragraph (1) of Law Number 17 Year 2016 concerning Child Protection? The conclusions of this paper are: (1) Protecting children is essentially protecting the family, protecting the community, and also protecting the nation. Therefore protection of children is very important. Including protection of children as victims of crime. Law Number 17 Year 2016 concerning Child Protection provides quite a lot of protection for children, even before the crime occurred in children, Law Number 17 Year 2016 which regulates Child Protection has provided protection for children not to become victims of a crime. (2) The imposing of a crime on a child must indeed be different from the imposing of a crime on an adult. Children are given the lightest possible punishment and half of the criminal convictions of adult criminal offenses. Children who violate the law of decency should be convicted with crimes that are educating and fostering children towards a better life, so that they become members of the community who obey the law. Therefore the nature of sanctions or actions for children must be different from the nature of criminal sanctions for adults. Criminal offense or action must be accountable and can benefit the child. This is to prevent unintended consequences that are detrimental to the child, so it needs to be considered an ethical basis for punishment that is justice as the only basis for punishment. The criminal must be educative, constructive, not destructive and must meet the interests of the child concerned. Keywords: Child Protection, Law Enforcement, Criminal Acts